New titanosauriform (Dinosauria: Sauropoda) specimens from the Upper Cretaceous Daijiaping Formation of southern China - Han, Fenglu (PeerJ, 2019)
Titanosauriform sauropod dinosaurs were once considered rare in the Upper Cretaceous of Asia, but a number of titanosauriforms from this stratigraphic interval have been discovered in China in recent years. In fact, all adequately known Cretaceous Asian sauropods are titanosauriforms, but only a few have been well studied, lending significance to any new anatomical information that can be extracted from Asia’s Cretaceous sauropod record. Here we give a detailed description of some titanosauriform bones recovered recently from the Upper Cretaceous Daijiaping Formation of Tianyuan County, Zhuzhou City, Hunan Province, southern China. The occurrence of this material in Hunan increases the known geographic range of titanosauriforms in eastern Asia. Although all of the specimens discussed in this paper can be assigned to Titanosauriformes at least tentatively, some bones display a limited number of features that are more typical of basal sauropods and/or derived diplodocoids, suggesting complex patterns of character evolution within Neosauropoda.